KEKUATAN HUKUM PENYELESAIAN PERSETUBUHAN DI LUAR PERKAWINAN YANG DISELESAIKAN SECARA HUKUM ADAT DESA SIOFABANUA - Yason Tanozisokhi Laia (LPPM Universitas Nias Raya, 2025)
The aim of this research is to find out the legal strength of the resolution of sexual intercourse outside of marriage which is resolved according to the customary law of Siofabanua Village. The type of research used is sociological or empirical legal research, namely examining applicable legal provisions based on existing facts in a society. Data collection was carried out using primary data, secondary data and tertiary data. obtained from secondary legal materials. The data analysis used is qualitative data analysis. Qualitative data analysis is carried out together with the data collection process. Based on the results of research conducted, the legal strength of the resolution of sexual intercourse outside of marriage which is resolved according to the customary law of Siofabanua Village is that the settlement can be carried out with the applicable provisions if the parties, both the perpetrator and the victim, are willing to resolve the case amicably. In resolving cases of sexual intercourse according to the customary law of the Siofabanua village, it is carried out through joint deliberation (Orahua) through the parties carried out by traditional leaders, religious leaders, government figures (village officials) by conducting negotiations on the problems that occur. If it has been resolved by mutual agreement, in this case the perpetrator of sexual intercourse may be subject to sanctions in the form of five million rupiah and three pigs with the aim of preventing a disturbance from occurring.